COSMOLOGICAL MODEL IN MODIFIED GRAVITY THEORY WITH NONMINIMAL COUPLING BETWEEN NONLINEAR ELECTRODYNAMICS AND EINSTEIN TENSORS - Yasir, Mhd.
This thesis focuses on the research on the theory of gravitational modification of the coupling between the energy-momentum tensor and the Einstein tensor. Furthermore, the cosmological applications of the theory are discussed. The method used in this study is nonminimal coupling, by considering the Friedmann-Robertson-Walker (FRW) spacetime metric. We then determine the final solution of the energy-momentum tensor. The final solution obtained for the matter sector is assumed to be nonlinear electrodynamics (NLED), which is related to the matter Lagrangian which is also assumed to follow the principles of nonlinear electrodynamics.